Preliminary observations on the nesting of the cupira bee (Partamona cupira Smith) in the Caatinga biome (Research, Society and Development, 2021)
Bees are the main and most effective agents of plant pollination, contributing to the stability of environments and agriculture and, in this way, favoring food security. Among indigenous bees, the Partamona cupira is one that has little information in the literature about its behavior and handling techniques. This work aimed to analyze the nesting choice of P. cupira, in its natural habitat, in the Caatinga biome, in relation to its magnetic orientation. This assessment was carried out at Sítio Farias, in the rural area of ​​the municipality of Pararí-PB. Field visits were carried out to identify and locate P. cupira nests in hosts. The results show that, in Cariri, Paraíba, P. cupira has a preference for nesting in abandoned termite mounds on the following hosts: catingueira (Poincianella bracteosa), 36.84%; dead fence (of any plant species), 21.05%; pear (Aspidosperma pyrifolium), 15.79%; mofumbu (Combretum leptostachyum), 10.52; umburana (Commiphora leptophloeos), 5.26%; umbu tree (Spondias tuberosa), 5.26%; and saw rosemary (Lipia gracilis), 5.26%. It is concluded that the P. cupira bee has a preference for nesting its nest - in plant hosts - in the Southwest (SW) direction.